Immunomodulatory Effect of Mesenchymal Stem Cells on B Cells - Franquesa, Marcella; Hoogduijn, Martin J.; Bestard, Oriol; Grinyó, Josep M. (Frontiers in Immunology, 2012)
The research on T cell immunosuppression therapies has attracted most of the attention in clinical transplantation. However, B cells and humoral immune responses are increasingly acknowledged as crucial mediators of chronic allograft rejection. Indeed, humoral immune responses can lead to renal allograft rejection even in patients whose cell-mediated immune responses are well controlled. On the other hand, newly studied B cell subsets with regulatory effects have been linked to tolerance achievement in transplantation. Better understanding of the regulatory and effector B cell responses may therefore lead to new therapeutic approaches. Mesenchymal Stem Cells (MSC) are arising as a potent therapeutic tool in transplantation due to their regenerative and immunomodulatory properties. The research on MSCs has mainly focused on their effects on T cells and although data regarding the modulatory effects of MSCs on alloantigen-specific humoral response in humans is scarce, it has been demonstrated that MSCs significantly affect B cell functioning. In the present review we will analyze and discuss the results in this field.